Molecular docking and antihypertensive effects of a novel angiotensin-I converting enzyme inhibitory peptide from yak bone - Gao, Xinchang; Bu, Fan; Yi, Dalong; Liu, Huaigao; Hou, Zhiying; Zhang, Chaoying; Wang, Chang; Lin, Jin-Ming; Dang, Yali; Zhao, Yufen (Frontiers in Nutrition, 2022)
A novel angiotensin-converting enzyme (ACE) inhibitory peptide SASVIPVSAVRA was purified and identified from yak bone by Electrospray Ionization-Time of Flight-Mass Spectrometry (ESI-TOF-MS). Results in vitro showed that the peptide exhibited strong ACE inhibition activities with an IC50 of 54.22 μM. Molecular docking results showed the binding between the peptide SASVIPVSAVRA and ACE mainly driven by van der Waals forces , hydrogen bonds and metal receptor. Interestingly, the ACE inhibition activities of the peptide increased about 19% after digestion, but none of its metabolites showed stronger activity than it. The in vivo experiment showed that the antihypertensive effect of peptide SASVIPVSAVRA at dose of 30 mg/kg is nearly equal to Captopril at dose of 10 mg/kg to spontaneously hypertensive rats (SHRs). The antihypertensive effect mechanism of SASVIPVSAVRA should be further studied through plasma metabolomics and bioanalysis. Structure analysis of amino acids and peptides produced during digestion may help better understand the antihypertensive effect of peptides.